The Impact of National Private Investment on Manufacturing in Egypt - Atlam, Baher Mohamed; Soltan, Ahmed Ashour; Mohamed, Noha Mohey (International Journal of Economics and Financial Issues, 2017)
This paper aims to present national private investment development phases and its contribution in manufacturing sector in Egypt. Moreover it devoted to examine the effect of national private investment on Egyptian manufacturing. Vector Auto Regressive analysis (VAR) was adopted based on yearly data for the period (1990-2015). Time series stationarity are checked by Augmented Dicky Fuller (ADF) test, and co- integration existence tested by Johansen co- integration test. The vector Error Correction model (VECM) utilized to check the existence of long run relationship between the manufactured product as a dependent variable and the national private investment as explanatory variable. Finally this paper concluded that, however national private investment contribute high share to manufacturing sector, the empirical analysis results obtained negative impact of this type of investment on manufacturing sector in short and long run. Keywords: national private investment, manufactured product, vector error correction model. JEL Classifications: E22, C22, L60, N67